Early gestational diagnosis of alobar holoprosencephaly with omphalocele: A case report - Frymonalitza, Ninda; Febriani, Febriani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Holoprosencephaly (HPE) is the most frequent congenital brain malformation, with alobar HPE representing the most severe form. It is often accompanied by other structural anomalies such as omphalocele, significantly complicating fetal prognosis and perinatal management. Purpose: To present the early gestational diagnosis of alobar holoprosencephaly with omphalocele. Method: A descriptive case report of a 40-year-old gravida 2 para 1 woman whose fetus was diagnosed via ultrasound at 17–18 weeks' gestation with alobar HPE and omphalocele. The case was managed through routine antenatal care and serial ultrasound monitoring. Results: Serial imaging revealed progressive ventriculomegaly and worsening abdominal wall defect. Despite the fatal nature of the anomalies, legal constraints in Indonesia prevented pregnancy termination. The fetus survived until intrauterine demise at 37–38 weeks, after which labor was induced and a stillborn delivered vaginally. Conclusion: This case underscores the importance of early gestational diagnosis and highlights the ethical and legal challenges in managing lethal fetal anomalies in restrictive settings. Comprehensive parental counseling and genetic evaluation are crucial components in delivering informed care.